Impact of short term intervention on mother knowledge, attitude and practice to improve oral hygiene of their children aged(4-7) Years Old in Al-Shaab Area - Baghdad City - Rajab, Manal Hadi; Ibrahim, . Mohammed Asaad (AL-Kindy College Medical Journal, 2016)
Background: Mothers are considered as the key role in effect on child's dental behavior. So it is important to involve her in oral health promotion program to prevent early childhood dental caries from occurring in early age. Objectives: To identify the knowledge, practice and attitude of mothers about the oral health of their children. And to measure the change in oral hygiene of children aged (4-7) years old after one month of interventional program on their mothers. Type of study: Non-randomized interventional.Methods: Non-randomized interventional study for one month in Al Shaab area in Baghdad to 65 mothers who have children aged (4-7) years .A modified administrated questionnaire is given to assess mothers’ knowledge, practice and attitude about their children’s oral hygiene. Loe and Silness index is used to measure the oral hygiene of their children through measure highly associated with oral hygiene of the children.Results: The study found the mothers level of education is not associated with their child's oral health behavior about brushing times and thumb sucking habit but it is highly associated with fluoride supplement for their children also mothers level of education and their attitude about fearing from dental treatment are not associated but are associated with their attitude about child's tooth pain.Conclusion: Improvement in oral hygiene of children after one month from receiving their mothers a short term oral hygiene program.